Political Economy of Village Fund and Socioeconomic Transformation of Communities in South Buton Regency - Zarni Adia Purna (Journal of Social Science and Economics (JOSSE), 2026)
This study examines the political economy of village fund implementation and its effects on the socioeconomic transformation of communities in South Buton Regency, Southeast Sulawesi Province, Indonesia. Village funds, disbursed under Law No. 6 of 2014 concerning Villages, represent the most significant transfer of fiscal resources to the village level in Indonesian history, yet their transformative impact is mediated by local political economy dynamics that remain poorly understood. Using a qualitative case study approach with in-depth interviews, focus group discussions, and document analysis, this research investigates how political economy factors, including elite capture, power relations, participatory governance, and inter-governmental coordination, shape the allocation and outcomes of village funds across six sub-districts in South Buton Regency. The findings reveal that village fund outcomes are significantly determined by the political economy of local governance: villages with stronger participatory planning processes, active village representative councils, and transparent financial management achieved substantially better socioeconomic outcomes than those where village funds were captured by local elites or dominated by the village head with limited accountability. Despite these political economy constraints, the data show measurable improvements in poverty reduction, infrastructure development, and small business growth across the regency between 2015 and 2023. The study contributes to the political economy of decentralization literature and offers practical recommendations for strengthening participatory governance mechanisms to maximize the socioeconomic transformation potential of village funds in island and coastal communities such as those in South Buton